A new, remarkable erigonine spider genus from eastern Asia (Araneae, Linyphiidae) - Tanasevitch, Andrei V. (Zootaxa, 2018)
Erigomicronus new genus is erected for Oreonetides longembolus Wunderlich & Li, 1995 (the type species) and Maro lautus Saito, 1984. The genitalia of both species are studied in detail and illustrated. Based to the male palp conformation, the new genus seems to belong to the subfamily Erigoninae, but the epigynum resembles that of some “micronetine” genera, e.g. Maro O. Pickard-Cambridge, 1906, Oreonetides Strand, 1901, etc., based on the presence of a scape-like projection in the epigynum. All records of M. lautus from Russia are erroneous and actually refer to O. longembolus.